MANAGEMENT OF MANDIBULAR FRACTURE IN LADY READING HOSPITAL PESHAWAR - Ahmad, Naseer; Javed, Muhammad; Ullah, Inayat (Journal of Postgraduate Medical Institute, 2011)
Objective: To find out the outcome of mandibular fracture managed by ENT surgeons in emergency situation in Lady Reading hospital Peshawar. Material and Methods: This prospective study was done in the department of ENT & Head and Neck Surgery LRH Peshawar from October 1995 to September 1996. We included in our study thirty patients of isolated mandible fracture, who came to our unit form emergency irrespective of cause, age and gender. We excluded all those patients who has had associated with other facial skeletal injuries. Results: Out of 30 patients, 25 (83.3%) were male and 5 (16.7%) were female ranging in age from 20 to 30 years. Road traffic accident was the most common cause (50%) and parasymphysial fracture was the most common (43.3%) site of fracture. Sixty percent (n=18) patients were treated with closed method and 33.3% (n=10) were treated with open method. Complications recorded were mild trismus in 20 cases (66.7%), bad scar formation in 8 cases (26.7%) and infection in five (16.7%) cases. Conclusion: In emergency situation when maxillofacial surgeons are not available, patients with maxillofacial trauma can be managed by ENT surgeons, with fair outcome